2018
DOI: 10.3389/fpls.2018.01836
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-Transferase Enzymes in Plant-Pathogen Interactions

Abstract: Plant glutathione S-transferases (GSTs) are ubiquitous and multifunctional enzymes encoded by large gene families. A characteristic feature of GST genes is their high inducibility by a wide range of stress conditions including biotic stress. Early studies on the role of GSTs in plant biotic stress showed that certain GST genes are specifically up-regulated by microbial infections. Later numerous transcriptome-wide investigations proved that distinct groups of GSTs are markedly induced in the early phase of bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
248
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(275 citation statements)
references
References 181 publications
(233 reference statements)
12
248
0
Order By: Relevance
“…Glutathione-S-transferases (GSTs), are well known for their detoxification activity of xenobiotics and endogenous toxic compounds in fungi by their conjugation to glutathione [75,76]. A GST gene, sscle_01g005000 was highly up-regulated (182-294 fold, l2fc 7.51-8.20) in our study (Table 3).…”
Section: Plos Onementioning
confidence: 53%
“…Glutathione-S-transferases (GSTs), are well known for their detoxification activity of xenobiotics and endogenous toxic compounds in fungi by their conjugation to glutathione [75,76]. A GST gene, sscle_01g005000 was highly up-regulated (182-294 fold, l2fc 7.51-8.20) in our study (Table 3).…”
Section: Plos Onementioning
confidence: 53%
“…It is involved in maize glutathione-S-tranferase (GST) protein expression which plays a role in plant defense for instance biotic stress [40]. Numerous studies have shown the induction of GSTs in early stages of bacterial, fungal, and viral infections and that silencing of these GSTs could modify disease symptoms and multiplication rates [41]. This putative candidate gene could play a role in MLN resistance as these GSTs can detoxify toxic substances that accumulate during infection by their conjugation with glutathione and attenuation of oxidative stress [41]; however, more research is needed to reveal the exact relevance of the GST gene in MLN resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The OBFs bind to a family of related, 20-bp DNA promoter sequences called ocs elements which bacterial and viral pathogens use to express genes in plants [43]. Moreover, the ocs elements also regulate the transcription of GSTs which involved in plant defense responses [41].…”
Section: Discussionmentioning
confidence: 99%
“…Their confirmed roles in biotic and abiotic stress tolerance are due to a detoxification capacity by conjugation with glutathione, the attenuation of oxidative damage and their contribution in hormone transport. The exact metabolic functions and their contribution to disease resistance in plants, however, remain to be elucidated (66).…”
Section: Resultsmentioning
confidence: 99%